To solve the addition \( 1 \frac{2}{6} + 6 \frac{3}{6} \), we can first convert the mixed numbers into improper fractions.
-
Convert \( 1 \frac{2}{6} \): \[ 1 \frac{2}{6} = \frac{1 \times 6 + 2}{6} = \frac{6 + 2}{6} = \frac{8}{6} \]
-
Convert \( 6 \frac{3}{6} \): \[ 6 \frac{3}{6} = \frac{6 \times 6 + 3}{6} = \frac{36 + 3}{6} = \frac{39}{6} \]
Now, we can add the two improper fractions: \[ \frac{8}{6} + \frac{39}{6} = \frac{8 + 39}{6} = \frac{47}{6} \]
Next, we can convert \( \frac{47}{6} \) back into a mixed number. We divide 47 by 6:
- \( 47 \div 6 = 7 \) with a remainder of \( 5 \).
So as a mixed number, \( \frac{47}{6} \) is: \[ 7 \frac{5}{6} \]
Thus, the result of \( 1 \frac{2}{6} + 6 \frac{3}{6} \) is: \[ \boxed{7 \frac{5}{6}} \]